Respons Netizen Terhadap Unggahan Lora Ismail Terkait Hadis ‘Ipar Adalah Maut’ Di Instagram (Gunung Djati Conference Series, 2025)
This study aims to analyze netizens' responses to Lora Ismail's Instagram post discussing thephenomenon of "Ipar is Death" from the perspective of hadith. This study is importantbecause social media, especially Instagram, has become the main space for discussingreligious issues, including sensitive topics such as the hadith "Ipar is Death". This study uses aqualitative method with a descriptive approach where data collection is carried outthrough observation and documentation of comments that appear on the post. Theanalysis used is sentiment analysis. The findings show that the majority of netizens gave apositive appreciation to this post, accompanied by follow-up questions, opinions, andadditional personal experiences that show the relevance of this hadith in everyday life, especially in maintaining boundaries with in-laws. The implications of this study are itscontribution to social media-based da'wah efforts, by providing new insights into howreligious content can be delivered contextually to be more relevant to digital audiences.The originality and value of this study lie in the focus of the analysis on one specific hadith inthe social media space, as well as how digital interactions create socio-religious dynamics.This provides a unique contribution to the study of digital da'wah and the use of socialmedia to spread religious teachings effectively